Shōjo Across Media
XIX, 397 p. 11 illus., 8 illus. in color.
Keywords: Since the 2000s, the Japanese word shōjo has gained global currency, accompanying the transcultural spread of other popular Japanese media such as manga and anime. The term refers to both a character type specifically, as well as commercial genres marketed to female audiences more generally. Through its diverse chapters this edited collection introduces the two main currents of shōjo research: on the one hand, historical investigations of Japan’s modern girl culture and its representations, informed by Japanese-studies and gender-studies concerns; on the other hand, explorations of the transcultural performativity of shōjo as a crafted concept and affect-prone code, shaped by media studies, genre theory, and fan-culture research. While acknowledging that shōjo has mediated multiple discourses throughout the twentieth century—discourses on Japan and its modernity, consumption and consumerism, non-hegemonic gender, and also technology—this volume shifts the focus to shōjo mediations, stretching from media by and for actual girls, to shōjo as media. As a result, the Japan-derived concept, while still situated, begins to offer possibilities for broader conceptualizations of girlness within the contemporary global digital mediascape.